Human mental workload : models and applications : first International Symposium, H-WORKLOAD 2017, Dublin, Ireland, June 28-30, 2017, Revised selected papers /: models and applications : first International Symposium, H-WORKLOAD 2017, Dublin, Ireland, June 28-30, 2017, Revised selected papers. (2017) - Unknown
No abstract available